A New Class of Meromorphically Analytic Functions with Applications to the Generalized Hypergeometric Functions. (12th September 2011) - Ghanim, Firas; Darus, Maslina
Abstract : We introduce a new subclass of meromorphically analytic functions, which is defined by means of a Hadamard product (or convolution). A characterization property such as the coefficient bound is obtained for this class. The other related properties, which are investigated in this paper, include the distortion and the radius of starlikeness. We also consider several applications of our main results to the generalized hypergeometric functions.